City scale related to epidermal growth factor receptor mutations status in Chinese non-small cell lung cancer - Guang-Gui Ding; Jie-Lun Wen; Rui Gong; Jiao-Jiao Yang; Wen-Jian Cen; Ling Deng; Fang Wang; Li-Yue Sun (Discover Oncology)
Abstract Purpose This study aimed to explore the relationship between city scale and epidermal growth factor receptor (EGFR) mutation status in Chinese patients with non-small cell lung cancer (NSCLC). Methods A retrospective study enrolled NSCLC patients who underwent tissue EGFR mutation testing at Sun Yat-sen University Cancer Center from 2012 to 2017. City scale was categorized according to classifications made by the State Council of China in 2014. Multivariable logistic regression was utilized to determine independent predictors of EGFR mutation status in NSCLC patients. Results A total of 4637 NSCLC patients were enrolled in this study. EGFR mutation related to gender, smoking statue, histological type, and city scale. Higher rate of EGFR mutations among patients of super large-sized and very large-sized cities compared to other cities. There was an inverse relationship between city scale and smoking status among patients. Multivariate analysis showed that city scale was not an independent predictor of EGFR mutation. Conclusions Although there is a correlation between the size of a city and the rates of EGFR mutations in Chinese NSCLC patients, city scale does not independently predict these mutation rates. Instead, the variations in EGFR mutation rates could be indirectly related to different levels of urbanization, which may influence smoking behaviors among the populations.